2011
DOI: 10.1108/17506141111163381
|View full text |Cite
|
Sign up to set email alerts
|

Economics, finance and development in China

Abstract: Purpose -The purpose of this paper is to construct a financial development index for China and to analyze the relationship between the financial sector development index and economic growth. Design/methodology/approach -This study uses Johansen-Juselius cointegration approach to determine long run relationship between variables. To determine the strength of causal relationship variance decomposition is used. The stability of coefficient is evaluated through rolling window regression method. Findings -The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
2
4
0
1
Order By: Relevance
“…Further a 1% increase in FDI impedes growth in real GDP by 0.254% in Bangladesh. This result is consistent with the earlier findings of Hye (2011) for India but not with those found by Ang (2007); Khan and Qayyum (2007); Kar et al (2008), and Hye and Dolgopolova (2011) for Malaysia, Pakistan, Turkey, and China respectively, on average ceteris paribus. These authors found that a 1% increase in FDI increases economic growth by 0.096, 1.029, 0.015 and 0.25%, respectively.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Further a 1% increase in FDI impedes growth in real GDP by 0.254% in Bangladesh. This result is consistent with the earlier findings of Hye (2011) for India but not with those found by Ang (2007); Khan and Qayyum (2007); Kar et al (2008), and Hye and Dolgopolova (2011) for Malaysia, Pakistan, Turkey, and China respectively, on average ceteris paribus. These authors found that a 1% increase in FDI increases economic growth by 0.096, 1.029, 0.015 and 0.25%, respectively.…”
Section: Resultssupporting
confidence: 94%
“…The results show that a 1 percent increase in RIR causes expected real economic growth to decline by 0.051%, ceteris paribus. This result is consistent with the findings of Hye (2011) for India but not with those found by Khan and Qayyum (2007) for Pakistan, and Hye and Dolgopolova (2011) for China. Hye's (2011) estimates suggest that a 1% increase in RIR lowers economic growth by 0.04% in India.…”
Section: Resultssupporting
confidence: 93%
“…Jeanneney et al (2006), in China, employed the generalized method of moments (GMM) system of innovation and observed positive influence of development on growth in country’s productivity in the financial sector . Hye and Dolgopolava (2011), in their research paper, employing Johansen Juselius Co-Integration approach, also confirmed the presence of cointegration between financial development index and growth in China’s economy. In Cameroon, with ARDL Bounds test, Puatwoe and Piabuo (2017) found the existence of statistically significant positive effect of all financial development indicators on economic growth.…”
Section: Literature Reviewmentioning
confidence: 68%
“…Untuk mengetahui pola interaksi antara seri data yang dapat dilihat, tes kausalitas Granger dilakukan selanjutnya. Metode yang dapat digunakan untuk melakukan uji kointegrasi adalah pengembangan dari uji kointegrasi di data time series, seperti metode yang menggunakan dasar test kointegrasi Engle-Granger dan Combined individual test Fisher/ Johansen (Misra & Trivedi, 2002;Muhammad Adnan Hye & Dolgopolova, 2011).…”
Section: Metode Penelitianunclassified